Method for separating and characterizing titanium dioxide nanoparticles and titanium ions
By combining the combined technology of size exclusion chromatography and inductively coupled plasma mass spectrometry, the problem of the existing technology being difficult to accurately separate and characterize small-sized TiO2 NPs and Ti ions is solved, and accurate quantitative analysis of these nanoparticles is achieved, supporting environmental risk assessment and wastewater treatment process design.
Patent Information
- Application Number
- CN202510115773.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to accurately separate and characterize titanium dioxide nanoparticles (TiO2 NPs) with particle sizes less than 40 nm and their titanium ions in ambient water bodies, making it difficult to assess their environmental risks and safety.
Size exclusion chromatography (SEC) combined with inductively coupled plasma mass spectrometry (ICP-MS) was used to separate and quantitatively analyze the water samples to be tested containing TiO2 NPs and Ti ions. Effective separation and quantitative determination of TiO2 NPs and Ti ions are achieved by optimizing the column type and mobile phase composition.
Accurate separation and quantitative analysis of TiO2 NPs and Ti ions with particle size less than 40nm is achieved, providing key data support for evaluating their environmental risks and safety, and helping to design wastewater treatment processes and achieve emission standards.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental analytical chemistry, and in particular relates to a method for separating and characterizing titanium dioxide nanoparticles and titanium ions. Background Art
[0002] Titanium dioxide nanoparticles (TiO2 NPs), as the most productive of all engineered nanomaterials (ENMs), have been widely used in a variety of industries, including paints and varnishes, textile brighteners, personal care products, and food. Due to their wide range of daily applications, TiO2 NPs are inevitably released into the environment. Studies have found that TiO2 NPs are released from textiles and personal care products during the washing process and are also detached from painted facades under natural weather conditions. Subsequently, these released TiO2 NPs can enter environmental water bodies through surface runoff. For example, TiO2 NPs from sunscreens have been detected in suspended matter from lakes, and TiO2 NPs with a size of 20-300 nm have been detected in surface runoff from aging building facades at a concentration of 8-10 μg / L. In addition, the environmental concentration of TiO2 NPs in urban runoff is between 5-150 μg / L. When TiO2 NPs enter environmental water bodies, the ecological and environmental risks and human health risks caused by them cannot be ignored.
[0003] TiO2 NPs of different morphologies can cause different toxic effects. For most engineered nanomaterials, particles with smaller particle sizes tend to produce more toxic side effects than particles with larger particle sizes, and TiO2 NPs are no exception. Studies have reported that small-sized TiO2 NPs with a particle size of 10-100nm can damage and cause rupture and leakage of human cell membranes, while TiO2 NPs with larger particle sizes (such as 110-300nm) are considered safe, indicating that the toxicity of TiO2 NPs increases with decreasing particle size. In addition, studies have also found that TiO2 NPs with a particle size of less than 40nm can induce genotoxic reactions in human bronchial epithelial cells. Since TiO2 NPs rarely dissolve and convert into Ti ion forms under natural environmental conditions, the toxic effects induced by TiO2 NPs are related to their ultrafine particle size rather than the Ti ions released by TiO2 NPs. Therefore, accurate determination of TiO2 NPs with a particle size of less than 40nm is of great significance for assessing their safety and environmental risks.
[0004] One of the current difficulties is the lack of appropriate methods to characterize and accurately quantify small-sized (less than 40 nm) TiO2 NPs in complex environments. Existing TiO2 NPs analysis methods mainly include microscopy and spectroscopy techniques, such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), and dynamic light scattering (DLS). Although these techniques can provide qualitative information such as the shape and size of nanoparticles, they cannot obtain accurate quantitative data, and due to matrix interference, they can easily affect their accurate determination in complex media. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a method for separating and characterizing titanium dioxide nanoparticles and titanium ions, in order to at least partially solve the above technical problems. The specific technical solutions provided by the present invention are as follows.
[0006] Specifically, the present invention provides a method for separating and characterizing titanium dioxide nanoparticles and titanium ions, comprising: using size exclusion chromatography to separate a water sample containing titanium dioxide nanoparticles and titanium ions to obtain a titanium dioxide nanoparticle component; and using inductively coupled plasma mass spectrometry to quantitatively test the concentration of titanium dioxide nanoparticles in the titanium dioxide nanoparticle component.
[0007] In an embodiment of the present invention, the difference in size between TiO2 NPs and Ti ions is used to separate the two, and the water sample to be tested containing titanium dioxide nanoparticles (TiO2 NPs) and titanium (Ti) ions is separated by size exclusion chromatography (SEC). During the separation process of the chromatographic column, TiO2 NPs and Ti ions will flow out at different times due to their different sizes, thereby obtaining a pure TiO2 NPs component. In complex environmental water samples or industrial wastewater samples, there are a variety of impurities and interfering substances. TiO2 NPs can be effectively separated from these complex mixtures by size exclusion chromatography, providing a basis for subsequent accurate analysis and testing. Inductively coupled plasma mass spectrometry (ICP-MS) is a highly sensitive and high-precision elemental analysis technology. It can perform quantitative analysis of elements, and when measuring the separated TiO2 NPs component, the concentration of TiO2 NPs in the TiO2 NPs component can be accurately determined. Accurate determination of TiO2 NPs concentration is crucial. Quantitative testing of TiO2 NPs concentration by ICP-MS can provide key data support for assessing its environmental risks. In complex environmental water samples or industrial wastewater samples, accurate TiO2 NPs concentration determination helps to design a reasonable wastewater treatment process to ensure that discharge standards are met. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1is a transmission electron microscope (TEM) image of the TiO2 NPs suspension in an embodiment of the present invention;
[0009] Figure 2 is a particle size distribution diagram obtained by Gaussian fitting of the TEM histogram of the TiO2 NPs suspension in the embodiment of the present invention;
[0010] Figure 3 This is a diagram showing the separation effect of TiO2 NPs by different types of fillers and chromatographic columns with different pore sizes in an embodiment of the present invention;
[0011] Figure 4 This is a diagram showing the separation effect of different types of fillers and chromatographic columns with different pore sizes on Ti ions in an embodiment of the present invention;
[0012] Figure 5 This is a diagram showing the separation effect of different salicylaldehyde oxime concentrations on TiO2 NPs in an embodiment of the present invention;
[0013] Figure 6 This is a graph showing the effect of different salicylaldehyde oxime concentrations on the recovery rate of TiO2 NPs in the examples of the present invention;
[0014] Figure 7 This is a diagram showing the separation effect of different salicylaldehyde oxime concentrations on Ti ions in an embodiment of the present invention;
[0015] Figure 8 This is a diagram showing the separation effect of different FL-70 concentrations on TiO2 NPs in an embodiment of the present invention;
[0016] Fig. 9 This is a graph showing the effect of different FL-70 concentrations on the recovery rate of TiO2 NPs in the examples of the present invention;
[0017] Fig.10 This is a diagram showing the separation effect of different FL-70 concentrations on Ti ions in an embodiment of the present invention;
[0018] Fig.11 This is a diagram showing the separation effect of TiO2 NPs under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention;
[0019] Fig.12 It is a linear fitting graph of different TiO2 NPs spike concentrations and signal responses under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention;
[0020] Fig.13 This is a diagram showing the separation effect of Ti ions under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention;
[0021] Fig.14 It is a linear fitting graph of different Ti ion spike concentrations and signal responses under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention;
[0022] Fig.15 This is a diagram showing the separation effect of different complexing agents as mobile phases on Ti ions under the condition that the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 2 of the present invention;
[0023] Fig.16 This is a diagram showing the separation effect of TiO2 NPs and Ti ions when different complexing agents are selected as mobile phases under the condition that the chromatographic column is an amino-modified chromatographic column with a pore size of 1000Å in Comparative Example 3 of the present invention;
[0024] Fig.17 This is a diagram showing the separation effect of TiO2 NPs and Ti ions in the standard sample of Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.
[0026] Titanium dioxide nanoparticles (TiO2 NPs) are widely used in consumer products. They are inevitably released into the environment, which has aroused great concern about their safety risks. Compared with larger TiO2 NPs (>90nm), smaller TiO2 NPs (less than 40nm) have a stronger ability to penetrate cell membranes and show more significant biotoxic effects. Currently, there are many techniques available for the analysis of TiO2 NPs. Among them, turbidity point extraction can separate and extract TiO2 NPs from environmental samples, but it cannot specifically distinguish small-sized (less than 40nm) TiO2 NPs. The single particle-inductively coupled plasma mass spectrometry (spICP-MS) method can obtain some information about the number concentration and size distribution of nanoparticles, but due to the limitation of instrument sensitivity, the particle size detection limit of TiO2 NPs is greater than 90nm, and TiO2 NPs with a particle size less than 90nm cannot be distinguished from Ti ions, which makes it difficult to accurately determine ultrafine TiO2 NPs (less than 40nm). However, although a variety of techniques are available for the analysis of larger TiO2 NPs (>90nm), analytical methods for smaller TiO2 NPs (less than 40nm) are still scarce. Therefore, it is necessary to develop a method that can accurately analyze small-sized (less than 40nm) TiO2 NPs.
[0027] Based on this, the present invention provides an online coupling technology (SEC-ICP-MS) of size exclusion chromatography (SEC) and inductively coupled plasma mass spectrometry (ICP-MS), which can simultaneously characterize and quantitatively analyze ultrafine particle size (10-40nm) TiO2 NPs and separate them from Ti ions.
[0028] Specifically, the present invention provides a method for separating and characterizing titanium dioxide nanoparticles and titanium ions, comprising: using size exclusion chromatography to separate a water sample containing titanium dioxide nanoparticles and titanium ions to obtain a titanium dioxide nanoparticle component; and using inductively coupled plasma mass spectrometry to quantitatively test the concentration of titanium dioxide nanoparticles in the titanium dioxide nanoparticle component.
[0029] In an embodiment of the present invention, the difference in size between TiO2 NPs and Ti ions is used to separate the two, and the water sample to be tested containing TiO2 NPs and Ti ions is separated by size exclusion chromatography (SEC). During the separation process of the chromatographic column, TiO2 NPs and Ti ions will flow out at different times due to their different sizes, thereby obtaining a pure TiO2 NPs component. In complex environmental water samples or industrial wastewater samples, there are a variety of impurities and interfering substances. TiO2 NPs can be effectively separated from these complex mixtures by size exclusion chromatography, providing a basis for subsequent accurate analysis and testing. Inductively coupled plasma mass spectrometry (ICP-MS) is a highly sensitive and high-precision elemental analysis technology. It can perform quantitative analysis of elements, and when measuring the separated TiO2 NPs component, the concentration of TiO2 NPs in the TiO2 NPs component can be accurately determined. Accurate determination of TiO2 NPs concentration is crucial. Quantitative testing of TiO2 NPs concentration by ICP-MS can provide key data support for assessing its environmental risks. In complex environmental water samples or industrial wastewater samples, accurate TiO2 NPs concentration determination helps to design a reasonable wastewater treatment process to ensure that discharge standards are met.
[0030] According to an embodiment of the present invention, separation of a water sample containing TiO2 NPs and Ti ions using size exclusion chromatography includes: passing the water sample into a chromatographic column, and achieving separation of TiO2 NPs and Ti ions by optimizing the type of chromatographic column and the type and concentration of mobile phase.
[0031] In an embodiment of the present invention, before optimizing the type of chromatographic column and the type and concentration of the mobile phase, a TiO2 NPs suspension is prepared. The uniformity of the TiO2 NPs suspension is a key prerequisite for quality control and method development. Commercial TiO2 powder contains not only small-sized nanoparticles, but also larger micron-sized particles. Since the main purpose of the present invention is to establish an analytical method for TiO2 NPs with a particle size of less than 40 nm, the commercial TiO2 powder is pretreated and a TiO2 NPs suspension is prepared for method performance testing and spiked environmental samples. Therefore, in order to separate nanoparticles with a particle size of less than 40 nm from the TiO2 powder, the TiO2 powder is dispersed in a 1-3% (v / v) FL-70 aqueous solution and subjected to ultrasonic dispersion treatment. Then, a low-speed (2000-5000 rpm) centrifugation is used for 20-40 min to allow larger particles to quickly settle to the bottom of the centrifuge tube, while smaller particles are dispersed in the supernatant. Next, the supernatant was collected and filtered, and the obtained filtrate was used as the TiO2 NPs suspension for subsequent use.
[0032] Specifically, the preparation process of TiO2 NPs suspension is as follows: TiO2 NPs powder (purchased from Sigma-Aldrich (St. Louis, Missouri, USA), with a nominal particle size of 21 nm) is dispersed in 2% (v / v) FL-70 solution, then ultrasonically dispersed, and then centrifuged at 5000 rpm for 20 min, and the supernatant is collected to remove large particle agglomerates. After that, the supernatant is filtered using a 0.2 μm filter membrane, and the filtrate is the TiO2 NPs suspension, which is used for method optimization and spike experiments.
[0033] The present invention adopts high-resolution transmission electron microscopy (HR-TEM, H-7500, Hitachi, Japan) to characterize the particle size distribution of TiO2 NPs suspension. The preparation method of HR-TEM sample is as follows: 5 μL TiO2 NPs suspension is dropped onto a copper grid, and then vacuum dried at room temperature for 8 h.
[0034] Figure 1 is a transmission electron microscope (TEM) image of the TiO2 NPs suspension in an embodiment of the present invention; Figure 2 This is a particle size distribution diagram obtained by Gaussian fitting of the TEM histogram of the TiO2 NPs suspension in the embodiment of the present invention.
[0035] like Figure 1As shown in Figure 2, TiO2 NPs present an irregular morphology. It is worth noting that during the preparation of transmission electron microscopy (TEM) samples, the drying process will inevitably cause some TiO2 NPs to aggregate and form agglomerates. Furthermore, by counting more than 300 particles, the particle size distribution was statistically analyzed and fitted using a Gaussian model. Figure 2 As shown, the particle size distribution of TiO2 NPs presents an approximately Gaussian distribution with a peak value of 20.7±4.5nm.
[0036] Furthermore, the Zeta potential of the TiO2 NPs suspension was measured (using a Malvern Nano ZS instrument (Malvern Instruments, UK)), and the measured value was -29.1±0.3 mV, indicating that the TiO2 NPs suspension prepared in the embodiment of the present invention was uniform and well dispersed.
[0037] According to an embodiment of the present invention, accurate quantification of the concentration of the prepared TiO2 NPs suspension is another key prerequisite for quality control and method development. Before the concentration of TiO2 NPs in the TiO2 NPs suspension is quantitatively tested using inductively coupled plasma mass spectrometry, the TiO2 NPs suspension is digested and acid-removed. The TiO2 NPs in the TiO2 NPs suspension are converted into Ti ions by digestion and acid-removal treatment, and the concentration of TiO2 NPs is calculated by measuring the concentration of Ti ions. The value can be traced back to the national primary standard material - titanium single element solution standard material (GBW 08689), ensuring the accuracy of the concentration value of the prepared TiO2 NPs suspension.
[0038] Specifically, the digestion and acid removal operations include: adding 5 mL of concentrated nitric acid (HNO3) and 1 mL of hydrogen fluoride (HF) to the TiO2 NPs suspension, using a microwave-assisted digestion instrument (CEM Mars 5, Xpress, Mathews, NC) for digestion, first at 150 ° C (800 W) for 10 min, and then at 190 ° C (1600 W) for 20 min. The mixed solution after digestion is then heated in a graphite furnace to remove the HF component from 150 ° C to 180 ° C. Finally, the mixed solution after acid removal is diluted with pure water and analyzed by ICP-MS.
[0039] According to an embodiment of the present invention, a mixed gas of oxygen and hydrogen is used as a collision reaction gas in the inductively coupled plasma mass spectrometry to avoid interference from calcium ions present in the TiO2 NPs component. 48 Ca isotopes will interfere 48 The determination of Ti 48Ti is the most abundant isotope of titanium (accounting for 73.72%). However, the concentration of Ca in environmental water is relatively high, which will seriously interfere with the quantitative analysis of Ti. Therefore, by using a mixed gas of oxygen and hydrogen as the collision reaction gas, 48 Ti + Ions can be converted into 48 Ti 16 O + ,and 48 Ca + The ions are converted into 48 Ca 16 O 1 H + Therefore, when monitoring in mass-shift mode 48 Ti + / 64 ( 48 Ti 16 O + )(Q1 / Q2), it can make the main source 48 The isotopic interference of Ca can be effectively eliminated. The relevant ICP-MS optimization detection parameters are listed in Table 1.
[0040] Table 1 Instrument parameters for ICP-MS detection
[0041]
[0042] According to an embodiment of the present invention, the mobile phase is a mixed solution of salicylaldehyde oxime and FL-70. Salicylaldehyde oxime (SO) is used as a coordination agent for Ti ions, and a nonionic surfactant FL-70 is used as a coating agent for TiO2 NPs. The nonionic surfactant FL-70 helps TiO2 NPs to elute from the chromatographic column by reducing the irreversible adsorption of TiO2 NPs on the chromatographic column filler; while the coordination agent SO is responsible for effectively forming a complex with the Ti ions on the TiO2 NPs and desorbing the Ti ions from the TiO2NPs, thereby eluting the Ti ions from the chromatographic column. Considering the complexing properties of SO and Ti ions, SO is used as a chelating agent for Ti ions. Therefore, a mixed solution of FL-70 and SO is selected as the mobile phase.
[0043] In some embodiments of the present invention, the effects of different types of fillers and chromatographic columns with different pore sizes on the separation effect were investigated, including amino, carboxyl and unmodified silica fillers, and chromatographic columns with pore sizes of 1000Å and 120Å, respectively. The type of chromatographic column in size exclusion chromatography is a key factor in separating nanoparticles (NPs) from their ionic states. Different filler types and pore sizes in the chromatographic column can significantly differ in the separation effect.
[0044] The SEC column conditions were optimized to identify the forms of TiO2 NPs and Ti ions. Therefore, 2% (v / v) FL-70 and 0.1% (m / v) SO were used as mobile phases. Different types of fillers and chromatographic columns with different pore sizes were used to separate and characterize TiO2 NPs and Ti ions with spiked concentrations of 212 ng / mL and 100 ng / mL, respectively. The specific test results are shown in the figure below. Figure 3-Figure 4 shown.
[0045] Figure 3 This is a diagram showing the separation effect of TiO2 NPs by different types of fillers and chromatographic columns with different pore sizes in an embodiment of the present invention; Figure 4 This is a diagram showing the separation effect of Ti ions using chromatographic columns with different types of fillers and different pore sizes in an embodiment of the present invention.
[0046] like Figure 3 and Figure 4As shown in the figure, the silica gel column with a pore size of 120Å can better characterize the forms of TiO2 NPs and Ti ions, which can be seen from the peak shape and narrow peak width of the chromatogram that are closer to Gaussian distribution, while the separation effect of the column with a pore size of 1000Å is poor. The study also found that the influence of the pore size of the column on the separation effect of different forms of Ti is greater than the influence of the filler type. The reason why the 120Å pore size column is better than the 1000Å pore size is that the path of TiO2NPs through the 120Å pore size column is more efficient, which can better separate TiO2NPs and Ti ions. Specifically, for the 1000Å pore size column, the size of 20nm TiO2NPs is smaller than the 1000Å pore size and can enter the pores of the column filler. The longer pore channel allows TiO2NPs to be retained in the 1000Å column for a longer time. However, since the pore size of the 120Å column is less than 20nm, TiO2 NPs cannot enter the pores of the column packing, but are directly eluted by the mobile phase through the gaps between the packings. At this time, the time and path of TiO2 NPs passing through the column are shorter. Therefore, the path of 20nm TiO2NPs in the 1000Å pore size column is longer, resulting in wider spectral peaks, and there are negative effects such as adsorption and mass loss of TiO2 NPs on the column packing. On the other hand, for both 120Å and 1000Å columns, the size of Ti ions is much smaller than the pore size of the column, so they will enter the channels in the packing pores and eventually be eluted by the mobile phase. Therefore, the difference in chromatographic peak width of Ti ions in 120Å and 1000Å columns is smaller than that of 20nm TiO2 NPs, but in the 120Å pore size column, the peak shape and peak width of Ti ions are better than those in the 1000Å pore size column. In addition, when using a silica gel column with carboxyl modified filler, the peak area of Ti ions and TiO2NPs is significantly lower than that of a 1000Å column with other fillers. This is because TiO2NPs are complexed with the carboxyl groups on the column filler, causing TiO2NPs to be retained in the column and difficult to be eluted by the mobile phase. Therefore, a silica gel column or an amino-modified silica gel column is selected, and the pore size of the column is 80-150Å, preferably a 120Å silica gel column. The separation of 10-40nm TiO2NPs and Ti ions in the water sample to be tested can be achieved by using a chromatographic column of this type and pore size.
[0047] Furthermore, in order to obtain the best separation effect of TiO2 NPs and Ti ions, the concentrations of salicylaldehyde oxime (SO) and FL-70 in the mobile phase were investigated.
[0048] A 120Å silica gel column was used with a mobile phase containing 2% (v / v) FL-70 and different SO concentrations to separate and characterize TiO2 NPs and Ti ions spiked with concentrations of 107 ng / mL and 50 ng / mL, respectively. The specific test results are shown in the figure. Figure 5-Figure 7 shown.
[0049] Figure 5 This is a diagram showing the separation effect of different salicylaldehyde oxime concentrations on TiO2 NPs in an embodiment of the present invention; Figure 6 This is a graph showing the effect of different salicylaldehyde oxime concentrations on the recovery rate of TiO2 NPs in the examples of the present invention; Figure 7 This is a diagram showing the separation effect of different salicylaldehyde oxime concentrations on Ti ions in an embodiment of the present invention.
[0050] like Figure 5-Figure 7 As shown, with the increase of SO concentration, the peak shape of the spiked Ti ions in the SEC-ICP-MS chromatogram changed from a chaotic multi-peak shape to a single peak shape close to Gaussian distribution. This indicates that in the low SO concentration range of 0.01-0.05% (m / v), the SO molecules in the mobile phase are not enough to complex with all Ti ions and elute simultaneously. The results showed that when the SO concentration was 0.01% (m / v), there was a difference in the retention time of Ti ions, resulting in the appearance of two peaks. As the SO concentration increased from 0.01% to 0.05%, the peak area of Ti ions at low retention times gradually decreased and tended to the main peak, indicating that with the increase of SO concentration, Ti ions tended to form a more uniform Ti ion-SO complex. When the SO concentration was ≥0.1%, the peak shape of Ti ions was close to a monodisperse Gaussian distribution, indicating that all Ti ions in the chromatographic column existed in the form of a uniform complex at this time. At different SO concentrations, the peak shape of TiO2 NPs showed a monodisperse Gaussian distribution. However, from Figure 6 It can be seen that the recovery rate of TiO2 NPs gradually increases as the SO concentration increases from 0.01% to 0.1%, but begins to decrease after the SO concentration exceeds 0.1%. The results show that at low SO concentrations (less than 0.1%), TiO2 NPs are difficult to completely elute from the SEC column. On the other hand, it was found in the experiment that too high SO concentration (0.2%) will cause it to form small oil droplets in the mobile phase, which require longer ultrasonic dispersion treatment to dissolve in the FL-70 aqueous solution. This 0.2% (m / v) SO component makes the physical state of the mobile phase solution unstable, resulting in a significant decrease in the recovery rate of TiO2 NPs. Based on the above separation and quantification results of TiO2 NPs and Ti ions, the concentration of salicylaldehyde oxime in the mobile phase is selected to be 0.05-0.14% (m / v), preferably 0.1% (m / v).
[0051] Furthermore, a 120Å silica gel column was used with a mobile phase containing 0.1% (m / v) SO and different FL-70 concentrations to separate and characterize TiO2 NPs and Ti ions with spiked concentrations of 107 ng / mL and 50 ng / mL, respectively. The specific test results are shown in the figure. Figure 8-Figure 10 shown.
[0052] Figure 8 This is a diagram showing the separation effect of different FL-70 concentrations on TiO2 NPs in an embodiment of the present invention; Fig. 9 This is a graph showing the effect of different FL-70 concentrations on the recovery rate of TiO2 NPs in the examples of the present invention; Fig.10 This is a diagram showing the separation effect of different FL-70 concentrations on Ti ions in an embodiment of the present invention.
[0053] like Figure 8-Figure 10 As shown in the figure, as the FL-70 concentration increases from 0.2% (v / v) to 2% (v / v), the peak area of TiO2 NPs in the SEC-ICP-MS chromatogram gradually increases, and the baseline gradually becomes stable. However, when the FL-70 concentration reaches 5% (v / v), the signal intensity of TiO2 NPs decreases significantly. This is because the high concentration of FL-70 causes the ICP-MS system pipeline to be blocked, making it difficult to detect the TiO2 NPs signal. This shows that 2% (v / v) FL-70 can effectively separate TiO2 NPs without reducing the signal intensity of the instrument. Fig. 9 It shows that as the FL-70 concentration increases from 0.2% (v / v) to 2% (v / v), the recovery rate of TiO2 NPs gradually increases from 65.9% to 106%, indicating that 2% (v / v) FL-70 can effectively elute all TiO2 NPs from the chromatographic column. When the FL-70 concentration is 5% (v / v), the signal intensity of TiO2 NPs decreases significantly, making it difficult to accurately characterize its peak area. Therefore, the recovery rate of TiO2 NPs is no longer calculated under the condition of 5% (v / v) FL-70. Similarly, Fig.10 It also shows that as the FL-70 concentration increases from 0.2% (v / v) to 2% (v / v), the baseline of Ti ions in the SEC-ICP-MS chromatogram gradually becomes smooth, while under 5% (v / v) FL-70 conditions, their signal intensity drops sharply, which is consistent with the change trend of TiO2 NPs. This result shows that 2% (v / v) FL-70 can effectively identify and separate Ti ions. Based on the above separation and quantification results of TiO2 NPs and Ti ions, the concentration of FL-70 in the mobile phase is selected to be 0.3-3% (v / v), preferably 2% (v / v).
[0054] The present invention is further described below by examples and related test experiments. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will. All instruments, consumables and reagents in the following examples, if not otherwise specified, may be obtained from commercial sources.
[0055] Comparative Example 1
[0056] In the early optimization process of this method, a large-scale screening of chromatographic columns and mobile phase compositions was carried out, especially the exploration of mobile phases for Ti ion separation, and finally the combination of FL-70 and salicylaldehyde oxime was selected.
[0057] A 120Å silica gel column was used with a mobile phase containing 2% (v / v) FL-70 to separate and characterize TiO2 NPs and Ti ions with spiked concentrations of 212 ng / mL and 51 ng / mL, respectively. The specific test results are shown in the figure. Figure 11-Figure 14 shown.
[0058] Fig.11 This is a diagram showing the separation effect of TiO2 NPs under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention; Fig.12 It is a linear fitting graph of different TiO2 NPs spike concentrations and signal responses under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention; Fig.13 This is a diagram showing the separation effect of Ti ions under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention; Fig.14 It is a linear fitting graph of different Ti ion spike concentrations and signal responses under the conditions that the mobile phase is 2% (v / v) FL-70 and the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 1 of the present invention.
[0059] like Figure 11-Figure 14As shown in the figure, from the perspective of chromatographic peak shape, both TiO2 NPs and Ti ions present a good Gaussian distribution; from the perspective of the integrated peak area after adding different concentrations, the actual added concentration is used as the horizontal axis and the signal response of the instrument is used as the vertical axis. TiO2 NPs have a good linear relationship, indicating that FL-70 is suitable for the quantification of the mass concentration of TiO2 NPs. However, the signal response of Ti ions does not show a good linear relationship with the actual concentration, indicating that 2% (v / v) FL-70 alone cannot elute Ti ions from the chromatographic column well. Therefore, FL-70 is selected as the mobile phase component for separating TiO2 NPs, and it is still necessary to continue to explore the mobile phase component suitable for separating Ti ions.
[0060] Comparative Example 2
[0061] The main reason for the poor quantitative effect of Ti ions is that the adsorption behavior of Ti ions by the chromatographic column filler is not linear. To solve this problem, the experiment used a Ti ion complexing agent to conduct a competitive adsorption strategy to overcome the filler adsorption problem. The experiment determined FL-70 as the mobile phase component of the TiO2 NPs eluent, and further screened complexes with hydroxyl, amino, and carboxyl functional groups that can complex Ti ions as mobile phase components to observe their separation of Ti ions.
[0062] A 120Å silica gel column was used, and 2mM sodium thiosulfate, 1mM sodium citrate, 1mM ascorbic acid, 0.1% (m / v) salicylaldehyde oxime and 2% (v / v) FL-70 were used as mobile phases to separate and characterize Ti ions spiked with a concentration of 100ng / mL. The specific test results are shown in the figure. Fig.15 shown.
[0063] Fig.15 This is a diagram showing the separation effect of different complexing agents as mobile phases on Ti ions under the condition that the chromatographic column is a silica gel chromatographic column with a pore size of 120Å in Comparative Example 2 of the present invention.
[0064] like Fig.15 As shown in the figure, the experiment found that using 0.1% (m / v) salicylaldehyde oxime as a complexing agent for Ti ions can well elute the Ti ions in the chromatographic column pipeline, while common metal ion complexing agents such as sodium thiosulfate, sodium citrate, and ascorbic acid cannot be used for chromatographic separation of Ti ions.
[0065] Comparative Example 3
[0066] In order to further optimize the peak effect of Ti ions, the experiment investigated the influence of different chromatographic column fillers. The experiment found that there was no significant difference in the separation effect of Ti ions between the 1000Å pore size amino-modified chromatographic column and the 120Å pore size silica gel chromatographic column (see Figure 4). Therefore, in the subsequent experiments to screen Ti ion mobile phase, the separation effect of the 1000Å pore size amino-modified chromatographic column on Ti ions was also investigated.
[0067] An amino-modified silica gel column with a pore size of 1000Å was used, and 0.1% (m / v) salicylaldehyde oxime, 1mM ascorbic acid, 1mM sodium citrate, 2mM sodium thiosulfate, 500ppm sodium fluoride, 0.1% triethanolamine and 2% (v / v) FL-70 were used as mobile phases to separate and characterize TiO2 NPs and Ti ions with spiked concentrations of 212ng / mL and 100ng / mL, respectively. The specific test results are shown in the figure. Fig.16 shown.
[0068] Fig.16 This is a diagram showing the separation effect of TiO2 NPs and Ti ions when different complexing agents are selected as mobile phases under the condition that the chromatographic column is an amino-modified chromatographic column with a pore size of 1000Å in Comparative Example 3 of the present invention.
[0069] like Fig.16 As shown in the figure, the experiment found that after investigating different types of mobile phases, salicylaldehyde oxime still had the best chromatographic separation effect on Ti ions, indicating that the 1000Å pore size amino-modified chromatographic column can also be used for the chromatographic separation of Ti ions. However, the chromatographic peak width of the separation of TiO2 NPs by this chromatographic column is relatively wide and has a certain tailing, and its separation effect is not as good as that of the 120Å pore size silica gel chromatographic column (such as Figure 3 ). Therefore, this method finally screened out FL-70 and salicylaldehyde oxime as the chromatographic separation mobile phases of TiO2 NPs and Ti ions, and the silica gel column with a pore size of 120Å was selected as the best chromatographic column type.
[0070] Example 1
[0071] In this Example 1, TiO2 NPs and Ti ions spiked with concentrations of 83 μg / L and 50 μg / L in the standard sample were separated by size exclusion chromatography (SEC) coupled with inductively coupled plasma mass spectrometry (ICP-MS). The coupled system includes a liquid chromatography (LC) separation system (Agilent 1260 series, Agilent Technologies, Palo Alto, CA) and an ICP-MS determination part (Agilent 8800). In the LC system, different forms of Ti (20 μL) in the standard sample were separated at 25°C using a silica gel column (Venusil XBP Silica, 4.6×250 mm, 5 μm particle size, 120Å pore size, Bona-Ajla Technology Co., Ltd., Tianjin, China), and the mobile phase was a mixed solution of 2% (v / v) FL-70 and 0.1% (m / v) SO at a flow rate of 0.5 mL / min.
[0072] TiO2 NPs (noted particle size 21 nm) were purchased from Sigma-Aldrich (St. Louis, MO, USA). The working solution of Ti ions (10 mg / L) was prepared by diluting a Ti standard solution (GBW 08689, National Institute of Metrology, China). FL-70, a mixture of nonionic and anionic surfactants, was purchased from Fisher Scientific (Fair Lawn, NJ, USA). Salicylaldehyde oxime (SO) was used as a chelating agent and was purchased from Alfa Aesar (Waltham, MA, USA). Ultrapure water (resistivity 18.2 MΩ cm) was prepared using a Milli-Q Gradient system (Millipore, Billerica, MA, USA).
[0073] Fig.17 This is a diagram showing the separation effect of TiO2 NPs and Ti ions in the standard sample in Example 1 of the present invention.
[0074] like Fig.17 It was shown that this method can effectively separate TiO2 NPs from Ti ions.
[0075] In order to investigate the reproducibility and accuracy of this method in separating and quantifying TiO2 NPs and Ti ions, the method performance was further evaluated in terms of retention time and concentration quantification of the target. The experimental results are shown in Table 2.
[0076] Table 2 Evaluation of analytical performance of separation of TiO2 NPs and Ti ions in Example 1
[0077]
[0078] a TiO2 NPs and Ti ions were measured at concentrations of 83 μg / L and 50 μg / L, respectively, and the experiment was repeated 6 times (n=6).
[0079] As can be seen from Table 2, the retention times of the two are 3.15min and 3.82min, respectively, indicating that the method for separating and characterizing TiO2 NPs and Ti ions provided by the present invention can efficiently identify and characterize TiO2 NPs and Ti ions with small particle size (10-40nm) within 5min. The retention time of TiO2 NPs and Ti ions detected by the method established by the present invention also has good precision, and the relative standard deviations (RSDs) of TiO2 NPs and Ti ions are 0.33% and 0.25%, respectively. In the quantitative analysis performance evaluation of the established method, 3 times the baseline noise (S / N=3) is used as the target detection limit (LOD), and the detection limits of TiO2 NPs and Ti ions are 3.72μg / L and 2.10μg / L, respectively. In addition, the linear correlation coefficients of TiO2 NPs and Ti ions in the concentration ranges of 17-333 μg / L and 10-100 μg / L are 0.9998 and 0.9992, respectively. It is worth noting that the recovery rate of Ti ions dropped below 70% when the spike concentration of Ti ions increased to 200 μg / L. This is because the limited amount of chelating agent SO (0.1% (m / v)) is insufficient to bind all Ti ions, resulting in the remaining spiked Ti ions adsorbed on the surface of the column packing and difficult to elute through the mobile phase. In view of the above reasons, and considering the instability of the mobile phase when the SO concentration exceeds 0.1%, the linear range of Ti ions was finally set to 10-100 μg / L as a compromise. The analytical performance parameters also showed that the spiked recoveries of TiO2 NPs and Ti ions were 103.5% and 101.2%, respectively, and the relative standard deviation (RSD) did not exceed 4% (n=6), as shown in Table 2. These results all indicate that the established method can quickly and accurately distinguish and quantify small-sized TiO2 NPs and Ti ions, showing stable and efficient method performance.
[0080] Example 2
[0081] This Example 2 uses the method in Example 1 to separate TiO2 NPs and Ti ions in actual environmental water samples.
[0082] Three real environmental water samples were collected from the river estuary of Jiaozhou Bay, Qingdao, China. The specific sampling locations are shown in Table 3. All water samples were collected in brown glass bottles, and the sampling bottles were cleaned three times with the corresponding water samples before collection. After collection, the water samples were stored in a refrigerator at 4°C. In order to investigate the possible interference introduced during sample collection, pretreatment and analysis, transportation blank and full process blank experiments were performed.
[0083] Table 3 Sampling points of rivers entering the Jiaozhou Bay in Example 2
[0084]
[0085] Since TiO2 NPs are not easily dissolved into Ti ion form in the real environment, it is more meaningful to measure the concentration of ultrafine TiO2 NPs with higher toxicity in the environment than to measure the concentration of Ti ions. In this example, the concentration of TiO2 NPs in three environmental water samples was monitored using the established method for separating and characterizing TiO2 NPs and Ti ions. The specific test results are shown in Table 4.
[0086] Table 4 Determination of TiO2 NPs concentration and spike recovery in three real environmental water samples (mean ± standard deviation, %, n=3)
[0087]
[0088] Not detected.
[0089] As shown in Table 4, no TiO2 NPs were detected in all the original water samples. After adding 17 μg / L and 33 μg / L of TiO2 NPs to the three environmental water samples, respectively, good recoveries were obtained in the samples of the Kamawan River (87.21% and 91.78%), the Moshui River estuary (86.57% and 94.94%), and the Loushan River estuary (82.75% and 95.09%). These results indicate that the established method is also accurate and applicable in the application of actual water samples. It should be noted that the target substances were not detected in the original water samples, indicating that the established method failed to detect ultrafine TiO2 NPs with a particle size as low as 20 nm, which are more toxic. However, the possibility of the presence of large-sized TiO2 NPs in the samples cannot be ruled out.
[0090] In summary, in order to solve the problem of accurate quantification of trace small-size (10-40nm) TiO2 nanoparticles (TiO2 NPs) in environmental water, this paper proposes a method for separation and characterization of TiO2 NPs and Ti ions based on SEC-ICP-MS. By using salicylaldehyde oxime as a chelating agent for Ti ions and FL-70 as a coating agent for TiO2 NPs, a mobile phase that can effectively solve the adsorption problem of different forms of Ti on the SEC column was prepared. By optimizing the SEC column type and the composition ratio of the mobile phase, the established method can simultaneously separate and quantify TiO2 NPs and Ti ions with a size as low as 20nm within 5 minutes, with detection limits of 3.72ng / mL and 2.10ng / mL, respectively. In addition, the spiked experiment of real environmental water samples showed that the spiked recovery rate of TiO2 NPs was between 82.75% and 95.09%, which verified the feasibility of this method. The present invention will open up a new approach for the quantitative analysis of small-sized (10-40 nm) TiO2 NPs and provide technical support for the quantitative analysis of other metal oxide nanoparticles.
[0091] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for separating and characterizing titanium dioxide nanoparticles and titanium ions, comprising: The water sample containing titanium dioxide nanoparticles and titanium ions is separated by size exclusion chromatography to obtain titanium dioxide nanoparticle components; The concentration of titanium dioxide nanoparticles in the titanium dioxide nanoparticle component is quantitatively tested by inductively coupled plasma mass spectrometry.
2. The method according to claim 1, wherein: The separation of water samples containing titanium dioxide nanoparticles and titanium ions by size exclusion chromatography includes: The water sample to be tested is passed into a chromatographic column, and the separation of the titanium dioxide nanoparticles and titanium ions is achieved by optimizing the type of the chromatographic column and the type and concentration of the mobile phase.
3. The method according to claim 2, wherein: The chromatographic column is a silica gel chromatographic column or an amino-modified silica gel chromatographic column.
4. The method according to claim 3, wherein: The pore size of the chromatographic column is 80-150Å.
5. The method according to claim 4, wherein: The particle size of the titanium dioxide nanoparticles in the water sample to be tested is 10-40 nm.
6. The method according to claim 2, wherein: The mobile phase is a mixed solution of salicylaldehyde oxime and FL-70.
7. The method according to claim 6, wherein: The concentration of salicylaldehyde oxime in the mobile phase is 0.05-0.14 m / v%.
8. The method according to claim 6, wherein: The concentration of FL-70 in the mobile phase is 0.3-3 v / v%.
9. The method according to claim 6, wherein: The concentration of salicylaldehyde oxime in the mobile phase is 0.1 m / v; The concentration of FL-70 in the mobile phase is 2 v / v%.
10. The method according to claim 1, wherein: In the inductively coupled plasma mass spectrometry, a mixed gas of oxygen and hydrogen is used as a collision reaction gas to avoid interference from calcium ions present in the titanium dioxide nanoparticle component.